Joubert Syndrome in Three Children in A Family: A Case Series - AKHONDIAN, Javad; ASHRAFZADEH, Farah; BEIRAGHI TOOSI, Mehran; MOAZEN, Nasrin; MOHAMMADPOOR, Toktam; KARAMI, Reza (Iranian Journal of Child Neurology, 2013)
Abstract How to Cite This Article: Akhondian J, Ashrafzadeh F, Beiraghi Toosi M, MOazen N, Mohammadpoor T, Karimi R. Joubert Syndrome in Three Children in a family: A Case Series. Iran J Child Neurol. 2013 Winter: 7(1); 39-42. Joubert syndrome (JS) is a rare autosomal recessive central nervous system malformation characterized by hypoplasia of the cerebellar vermis, hypotonia and abnormal psychomotor development, along with altered respiratory pattern and various ophthalmologic features. Here, we describe three children with Joubert syndrome in a family that had almost similar presentations, including ataxia, developmental delay, mental retardation and ocular disorders. Prevalence of Joubert syndrome is about 1 in 100,000 live birth. It may be accompanied by other organs’ disorders. The molar tooth sign is pathognomonic for joubert syndrome that is ascertained by brain MRI. References 1. Ahmed J, Ali US. Joubert syndrome with nephronophthisis in neurofibromatosis type 1. Saudi J Kidney Dis Transpl 2011;22(4):788-91. 2. Singh P, Goraya JS, Saggar K, Ahluwalia A. A report of Joubert syndrome in an infant, with literature review. J Pediatr Neurosci 2011;6(1):44-7. 3. Brancati F, Dallapiccola B, Valente EM. Joubert Syndrome and related disorders. Orphanet J Rare Dis 2010;5:20. 4. Malaki M, Nemati M, Shoaran M. Joubert syndrome presenting as unilateral dysplastic kidney, hypotonia, and respiratory problem. Saudi J Kidney Dis Transpl 201;23(2):325-9. 5. Louie CM, Gleeson JG. Genetic basis of Joubert syndrome and related disorders of cerebellar development. Hum Mol Genet 2005; 15;14 Spec No. 2:R235-42. 6. Gill H, Muthusamy B, Atan D, Williams C, Ellis M. Joubert syndrome presenting with motor delay and oculomotor apraxia. Case Rep Pediatr 2011;2011:262641. 7. Duldulao NA, Lee S, Sun Z. Cilia localization is essential for in vivo functions of the Joubert syndrome protein Arl13b/Scorpion. Development 2009;136(23):4033-42. 8. Parisi MA. Clinical and molecular features of Joubert syndrome and related disorders. Am J Med Genet C Semin Med Genet. 2009;15;151C(4):326-40. 9. Castori M, Valente EM, Donati MA, Salvi S, Fazzi E, Procopio E, et al. NPHP1 gene deletion is a rare cause of Joubert syndrome related disorders. J Med Genet 2005;42(2):e9. 10. Maria BL, Hoang KB, Tusa RJ, Mancuso AA, Hamed LM, Quisling RG, et al. “Joubert syndrome” revisited: key ocular motor signs with magnetic resonance imaging correlation. J Child Neurol 1997;12(7):423–30.